Do radiative losses determine the characteristic emission of the blazar Mkn 421? - Baheeja, C.; Sahayanathan, S; Rieger, Frank M.; Jagan, Sitha K.; Ravikumar, C. D. (Monthly notices of the Royal Astronomical Society, 2022)
The radiative loss interpretation for the broken power-law spectra of blazars is often questioned since the difference between the indices does not support this inference. Using the blazar Mkn 421 as a case study, we performed a detailed analysis of its characteristic photon energy where the spectral index changes significantly. We used the observations of the source by Swift-XRT from 2008 to 2019 to identify the characteristic photon energy and the corresponding spectral indices. The spectra in the energy range 0.3-10.0 keV can be well fitted by a log parabola as well as a smooth broken power law. From the smooth broken power-law spectral fit, we show that the spectral indices before and after the characteristic photon energy are strongly anticorrelated. Further, the spectral curvature measured at the characteristic photon energy indicates an anticorrelation with the low-energy spectral index while the high-energy spectral index shows a positive correlation. These findings are at variance with a simple radiative loss interpretation for the characteristic photon energy, and alternative scenarios are thus discussed. Though these scenarios are, in principle, capable of reproducing the correlation results, they deviate significantly from the observed properties.
Gesehen am 24.08.2022